Effect of Commercial Baker’s Yeast Supplementation (Saccharomyces Cerevisiae) in Diet and Drinking Water on Productive Performance, Carcass Traits, Haematology and Microbiological characteristics of Local Quails - Rebin A. Mirza; Sheren Dh. Muhammad; Karwan Y. Kareem (Zanco Journal of Pure and Applied Sciences, 2020)
The research was conducted to assess the impact of supplementation of Saccharomyces cerevisiae (SC) on the quality of products, intestinal microbiota, haematology parameters and histology of local quail. A number of 99 days old quails were randomly assigned and divided into three treatments in triplicate which contained 33 birds in each treatment for 42 days experimental period. Design of the dietary treatments was formulated as followings; control (T1) basal diet, 1% of SC in basal diet (T2) and 1% of SC in drinking water (T3). The results of this study revealed that addition and supplementation of SC had positive impact on blood biochemical profile and products quality of local quails. The contents of beneficial bacteria (Lactobacillus spp.) in caecal digesta was increased in both treatment of adding SC in diet and drinking water, while the coliform bacteria significantly (p<0.05) decreased in comparison to the control group. Also, Supplementation of SC in diet and drinking water substantially increased number of lymphocyte and lowered H/L (Heterophil/Lymphocyte) ratio comparing to control treatment at the final stage of the study. No significant (p>0.05) differences was seen regarding carcass traits of the treated quails. To summarize, baker’s yeast supplementation in the diet and drinking water of quails substantially improved production performance, gut microbiota and hematology parameters of local quails.